Physico-Mechanical properties of the Josapine Pineapple Fruits. - Shamsuddin, Rosnah; Wan Daud, Wan Ramli; Takrif, Mohd Sobri; Hassan, Osman (Universiti Putra Malaysia Press, 2009)
The physico-mechanical properties data of fruits are important in the design of various handling, packing, and storage and transportation system. The physical-mechanical properties of pineapple fruit from the Josapine variety, namely the weight of the fruit (with and without peel), pulp to peel ratio, diameter of the whole fruit (with and without peel), at three different positions along the longitudinal axis of the fruit, length of the fruit (with and without peel) and the length of crown were studied using the standard method at seven stages of maturity during storage at 25°C and 52% (RH). The effect of fruit maturity on the firmness of each fruit at three different locations was measured using a cylindrical die of 6 mm in diameter with the Instron Universal Testing Machine. The results indicated that the average total weight of a single fruit is 886.86±49.67 g. The average pulp to peel ratio is 1.91. The average diameter (with and without peel) was 86.83±5.24 mm and 80.95±4.15 mm (top section), 100.77±3.84 mm and 90.19±3.73 mm (middle section) and 97.17±3.49 mm and 73.30±5.11 mm (bottom section), respectively. The average length of the fruit (with and without peel) was 126.65 mm and 113.64 mm, respectively. The average length of crown was 89.13 mm. The firmness of the fruits was found to decrease with the stage of maturity. These data are important in determining the optimum stage of maturity for fruit processing.